Antiphospholipid antibodies are associated with positive screening for common mental disorders in women with previous pregnancy loss. The NOHA-PSY observational study. (2nd January 2019) - Gris, Jean-Christophe; Cyprien, Fabienne; Bouvier, Sylvie; Cochery-Nouvellon, Eva; Lavigne-Lissalde, Géraldine; Mercier, Erick; Balducchi, Jean-Pierre
Abstract: Objectives: Case reports describe neuropsychiatric manifestations associated with antiphospholipid antibodies (aPlAbs). In patients sharing the same symptoms fulfilling the antiphospholipid syndrome (APS) clinical criteria, the prevalence of common mental disorders has, however, never been studied. Methods: We observed women with three consecutive abortions before the 10th week of gestation or one foetal loss at or beyond the 10th week. We compared the prevalence of common psychiatric disorders detected through screening using the Mini International Neuropsychiatric Interview, 10 years after inclusion, in women with APS ( n  = 506), women negative for aPlAbs but carrying the F5 rs6025 or F2 rs1799963 thrombogenic polymorphism ( n  = 269), and women with negative thrombophilia screening results as controls ( n  = 764). Results: Similar prevalence values were obtained for controls and women bearing one of the two thrombogenic polymorphisms. Women with APS more frequently had mood disorders (relative risk (RR) 1.57 (1.262–1.953), P  = .0001) and anxiety (RR 1.645 (1.366–1.979), P  < .0001). Within the APS group, lupus anticoagulant (LA) and anti-β2GP1 IgG, or triple positivity, were strong risk factors for mood disorders. Conclusions: Women with obstetric APS have a higher risk of positive screening for common mental disorders than women without APS.